Contribution of Total Screen/Online-Course Time to Asthenopia in Children During COVID-19 Pandemic via Influencing Psychological Stress - Li, Lin; Zhang, Jing; Chen, Moxin; Li, Xue; Chu, Qiao; Jiang, Run; Liu, Zhihao; Zhang, Lili; Shi, Jun; Wang, Yi; Zhu, Weizhong; Chen, Jian; et al. (Frontiers in Public Health, 2021)
Objectives: During the coronavirus disease 2019 (COVID-19) self-quarantine period, the transition to online-course has profoundly changed learning modes of millions of school-aged children and put them at an increased risk of asthenopia. Therefore, we aimed to determine associations of total screen/online-course time with asthenopia prevalence among that children during COVID-19 pandemic, and whether the associations are mediated by psychological stress. Methods: Asthenopia was defined according to a validated computer vision syndrome questionnaire (CVS-Q). We used CVS-Q to collect frequency and intensity of 16 asthenopia-related eye symptoms of 25,781 children. Additional information, including demographic features, eye care habits, visual disorders, lifestyle, psychological and environmental factors, were also collected. Results: The overall asthenopia prevalence was 12.1%, varying from 5.4%-18.2% across grade/sex-classified subgroups. A 100-hour increment of total screen/online-course time were associated with an increased risk of asthenopia by 9% [odds ratio (OR) = 1.09] and 11% (OR = 1.11), respectively. Mediation analysis showed that the proportions of total effects mediated by psychological stress were 23.5% and 38.1%, respectively. Age, female sex, having myopia or astigmatism, bad habits when watching screens were also risk factors. Conversely, keeping 34-65 cm between eyes and screen, increased rest time between classes, and increased eye exercise frequency were associated with a decreased risk. Discussion: Our study indicates that the influence of long total screen or online-course time on psychological stress increases asthenopia risk. This study’s findings provide a new avenue for intervening screen-related asthenopia in addition to incorporating a reasonable schedule of online courses into educational policy.